2020
DOI: 10.18844/gjbem.v10i3.4686
|View full text |Cite
|
Sign up to set email alerts
|

Tourism contribution to Gross Domestic Product (GDP) and Gross Value Added (GVA)

Abstract: The overall evolution of the economy is usually appreciated by two macroeconomic indicators GDP and GVA, which by their value gives us clear information on the state of the economy.  Gross domestic product (GDP), the main macroeconomic aggregate of national accounts, is the final result of the production activity of resident producer units and which corresponds to the value of goods and services produced by these units for final consumption. Gross Value Added (GVA) is the balance of the production account and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Anda et al calculated the tourism value added in Romania from 2008 to 2014 through the Tourism Satellite Account. The results show that the tourism value added in Romania accounted for 2.1% of its GDP in 2014 [41]. Using the input-output table, Zeng and Cai measured the tourism value added in 30 provincial regions (not including the Tibet Autonomous Region) in mainland China in 2000 and 2005, which were 389.083 billion yuan and 860.345 billion yuan, respectively, and found that the contribution rate of the tourism industry in most regions was concentrated in 3-8% [42].…”
Section: Literature Reviewmentioning
confidence: 97%
“…Anda et al calculated the tourism value added in Romania from 2008 to 2014 through the Tourism Satellite Account. The results show that the tourism value added in Romania accounted for 2.1% of its GDP in 2014 [41]. Using the input-output table, Zeng and Cai measured the tourism value added in 30 provincial regions (not including the Tibet Autonomous Region) in mainland China in 2000 and 2005, which were 389.083 billion yuan and 860.345 billion yuan, respectively, and found that the contribution rate of the tourism industry in most regions was concentrated in 3-8% [42].…”
Section: Literature Reviewmentioning
confidence: 97%
“…In the business world, global competition and increasing consumer environmental awareness drive businesses to adopt green management approaches (Zhu et al, 2005). Tourism contributes to approximately 10% of the global gross domestic product and significantly influences the economic development of developing countries at tourist destinations (Anda et al, 2020). However, uncontrolled tourism development and unsustainable management policies can negatively affect the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one of the most important functions required by the life we live in is continuous learning. While teaching activities are given formally in educational institutions, it is known that the teaching function can be performed with different teaching methods with the developing technology [4] [29]. At the moment of using information and technology, while tools such as letters, newspapers, radio, and television are used, it is known that computers, smartphones, especially the internet have a much more important place at the moment [15].…”
Section: Introductionmentioning
confidence: 99%